Genetic Determination and Clonal Relationships of Staphylococcus aureus Isolated from Dairy Cows in Baturraden, Central Java, Indonesia - Fatkhanuddin Aziz; Siti Isrina Oktavia Salasia; Mitra Slipranata (Universitas Gadjah Mada, 2014)
Cases of mastitis in cows at Baturraden are leading to signifi cant and ongoing problems due to reducedproduction and lower milk quality. This study was designed to identify which of selected virulence determinantgenes of S. aureus are involved in the Baturraden infection, and to determine the clonal relationship amongthese isolates. Seventeen isolates were identifi ed as S. aureus based on their biochemical properties and speciesspecifi city for 23S rRNA and nuc genes. S. aureus isolates were genotypically characterized for the selectedvirulence determinants: coa, clfA, fnbA, fnbB, cap5, spa IgG and spa X- region genes. Clonal relationship analysisamong isolates was carried out using AFLP and results compared with previously confi rmed relationshipsbetween selected S. aureus isolated from other regions. The results show that eight isolates contain all thegenes, but six isolates lack fnbB and two isolates lack cap5 genes. AFLP analysis showed that all isolates of S.aureus originating from cows in Baturraden belong to one cluster. This study provides additional knowledgeabout S. aureus infection in Baturraden cows, including the number of virulence determinant genes that mayplay a role in pathogenicity.